Survey Sondage : Realism(e)s 70. - Amaya, Mario; The Montreal Museum of Fine Arts, Toronto; Art Gallery of Ontario, Toronto (Montreal : The Montreal Museum of Fine Arts, 1970)
Bonham, Don ; Boyle, John ; Brown, D.P. ; Burton, Dennis ; Chambers, John ; Curnoe, Greg ; Dale, Jack ; van Dalen, Anton ; Danby, Ken ; Davis, John Craig ; Dean, T.G. ; Dery, François ; Eyre, Ivan ; Fafard, Joseph ; Falk, Gathie ; Gilhooly, David ; Hogenkamp, Claire ; Leonard, John C. ; Levine, Marilyn ; Lewis, Glenn ; Lindner, Ernest ; MacGregor, John ; Mackenzie, Hugh ; Mackenzie, Robin ; Miller, Archie ; Molnar, Frank ; Morris, Michael ; N.E. Thing Co. ; de Niverville, Louis ; Ondaatje, Kim ; Onley, Toni ; Prent, Mark ; Prodnuk, Frank G. ; Sasaki, Tomiyo ; Sawatsky, N.J. ; Sawchuk, George ; Senitt-Harbison, Cathy ; Sewell, R.G. ; Smith, John Ivor ; Snow, Michael ; Tapanila, Jack ; Urquhart, Tony ; Vazan, William ; Venor, Robert ; Warkov, Esther ; Wieland, Joyce
Frans & Engels
Survey Sondage : Realism(e)s 70, The Montréal Museum of Fine Arts, Montréal ; May 8 - June 7, 1970 ; Art Gallery of Ontario, Toronto, August 7 - September 6, 1970
boek